Antibiotic-induced mitochondrial dysfunction : Exploring tissue-specific effects on HEI-OC1 cells and peripheral blood mononuclear cells - Liu, Tianshi; Chamkha, Imen; Elmér, Eskil ; 0000-0001-7901-1826; Sjövall, Fredrik ; 0000-0001-5612-0325; Ehinger, Johannes K. ; 0000-0002-2417-5767 (Biochimica et Biophysica Acta - General Subjects, 2025)
Antibiotics are crucial in treating infectious diseases, particularly in intensive care unit patients, but they can lead to side effects such as ototoxicity. A mechanism for this is antibiotics targeting mitochondrial components in eucaryotic cells, due to their resemblance of those in bacteria. Here we investigate how five classes of antibiotics (carbapenems, fluoroquinolones, aminoglycosides, glycopeptides, and oxazolidinones) affect mitochondrial respiratory function, ATP levels, mitochondrial membrane potential and levels of reactive oxygen species in an inner-ear derived epithelial cell line (HEI-OC1) and human primary blood cells (PBMCs) at clinically relevant concentrations. Mitochondrial respiration in intact HEI-OC1 cells was suppressed in response to the majority of the tested antibiotics. This effect was lost when the HEI-OC1 cells were permeabilized and substrate supply controlled. Further in these cells, ROS levels were increased and ATP levels reduced. In contrast, no measure of mitochondrial function of PBMCs was affected by any antibiotics at the same concentration. We show that HEI-OC1 cells are sensitive to a broad range of antibiotics, and that the mechanism of toxicity to mitochondrial respiration is upstream of the mitochondrial respiratory chain, with downstream effects on mitochondrial respiration, ATP levels and ROS levels.
Publisher Copyright: © 2025
Keywords: Antibiotics; ATP production; HEI-OC1 cells; Mitochondrial dysfunction; Ototoxicity; PBMCs; Reactive oxygen species